Ethics Understanding and Organizational Support as Drivers to Blowing the Whistle - Kemalasari, Yunita Andi; Yunus, Erlinda Nusron (Business Review and Case Studies, 2024)
Background: There are still pros and cons regarding the courage to report unethical practices known to the organization (whistleblowing). This study focuses on knowing the effect of different levels of ethical understanding of employees in reporting unethical behavior or experiences that they know. Purpose: This study aims to determine the effect of different perceptions on organizational support in reporting known unethical behavior or experiences. Design/methodology/approach: This research was conducted using an experimental method on 40 participants, so that it can be tested for differences in the level of ethical understanding and perceptions of organizational support for being a reporter. Findings/results: The results indicate that there is not enough evidence to support H1 and H2. After receiving information that H1 and H2 were rejected, the researchers explored more in-depth information through the Focus Group Discussion (FGD) method. Personality factors and individual values encourage participants to report unethical behavior or experiences known to employees. Participants feel less likely to report unethical behavior, to avoid conflict and not want to reveal the disgrace of their department. Some participants preferred to keep themselves and the rest felt that unethical practices were common practice in organizations. Conclusion: There are several characteristics of the reporter, such as loyalty to the organization, role, and position as well as other personal characteristics such as gender, tenure, and seniority. This is in line with the results of extracting information obtained through the focus group discussion (FGD) method from 6 willing participants. In the context of research, this can be explored more deeply. Related to the rejection of the hypothesis in this study, further research can explore some of the things found in the FGD results, such as individual values, personality factors, concerns about being a reporter, or other sides that are more encouraging to report unethical behavior or experiences known to employees. Originality/value (state of the art): This research can contribute and add scientific insight to business ethics with findings regarding whistleblowing of employees in companies from eastern developing countries (Indonesia), which have different cultural tools from western countries. Keywords: business ethics, ethics understanding, experimental research, organizational support, whistleblowing